Dermatology Emergencies. Issue 3 (May 2018) - Kellen, Roselyn; Berlin, Joshua M.
Abstract : ABSTRACT: Dermatology is primarily an outpatient specialty. However, it is important to recognize certain conditions that require referral for inpatient management as well as for healthcare professionals to appreciate the types of patients who need to be triaged appropriately in the emergency room or urgent care setting. This article will serve to summarize some of the diagnostic features and management of these patients.